Investigation of Carbapenemases in Carbapenem-Resistant Escherichia coli and Klebsiella pneumoniae Strains Isolated in 2014 in Turkey - HASDEMİR GÖKBOĞA, MÜNEVVER UFUK (ANKARA MICROBIOLOGY SOC, 2016)
Carbapenems are the choice of treatment in infections caused by multidrug resistant Enterobacteriaceae. In recent years carbapenem-resistant Enterobacteriaceae isolates due to carbapenemases have been increasingly reported worldwide. Multicenter studies on carbapenemases are scarce in Turkey. The aim of this study was to determine the distribution of carbapenemases from different parts of Turkey as a part of the European Survey of Carbapenemase Producing Enterobacteriaceae (EuSCAPE) project. Beginning in November 2013, carbapenem-resistant isolates resistant to at least one of the agents, namely imipenem, meropenem, and ertapenem were sent to the coordinating center. Minimum inhibitory concentrations for these carbapenems were determined by microdilution tests following EUCAST guidelines. Production of carbapenemase was confirmed by combination disk synergy tests. Types of carbapenemases were investigated using specific primers for VIM, IMP; NDM, KPC and OXA-48 genes by multiplex polymerase chain reaction. In a six month period, 155 suspected carbapenemase-positive isolates were sent to the coordinating center of which 21 (13.5%) were E.coli and 134 (86.5%) were K.pneumoniae. Nineteen (90.5%) strains among E.coli and 124 (92.5%) strains among K.pneumoniae were shown to harbour at least one carbapenemase gene by molecular tests, with a total of 92.3% (143/155). Carbapenemases were determined as a single enzyme in 136 strains (OXA-48: 84.6%; NDM: 6.3%; VIM: 2.8%; IMP: 1.4%) and as a combination in seven isolates (OXA-48 + NDM: 2.1%; OXA-48 + VIM: 2.1%; VIM + NDM: 0.7%). KPC was not detected in any of the isolates. According to the microdilution test results, resistance to imipenem, meropenem and ertapenem in OXA-48 isolates were 59.5%, 52.9% and 100%, respectively. The combination disk synergy test was 100% compatible with the molecular test results. As most of the OXA-48 producing isolates were susceptible to meropenem but all were resistant to ertapenem, ertapenem seems to be the most sensitive agent in screening carbapenemases in areas where OXA-48 is prevalent and phenotypic combination tests can be useful in centers where molecular tests are not available.
Keywords: Carbapenemase; Enterobacteriaceae; OXA-48; metallo-beta-lactamase; Turkey; METALLO-BETA-LACTAMASES; ENTEROBACTERIACEAE; SPREAD; TEMOCILLIN; PRODUCERS; EMERGENCE; ISTANBUL; KPC